NEGATIVE IMPACT PREVENTION TO THE ENVIRONMENT ON ILLEGAL COMMUNITY MINING TOWARD COMMAND AND CONTROL APPROACH - fenty u puluhulawa (Faculty of Law, Universitas Jenderal Soedirman, 2015)
This article aims to analyze the need for local government policies to curb the problem of mining area which is illegally indicated. This study uses normative juridical approach. The results showed the need to command and control approach in solving the problem of artisanal mining. Artisanal mining which is doing illegally potentially damaging to the environment, conflict potentially and other negative impacts, so it needs to be managed according to the legislation. Therefore, the role of local government is required to minimize the impact caused by illegal gold mining activities. This approach is expected to control illegal mining through regulatory mechanisms, as well as an active role in conducting surveillance. This approach is expected to provide legal certainty for artisanal mining.Keywords: command and control, illegal mining